PARENTS' EFFORTS TO IMPROVE THE UNDERSTANDING IN CARING FOR CHILDREN WITH MENTAL RETARDATION - Aulia Nailul Muna; Sunardi Sunardi; Herry Widyastono (STKIP Melawi, 2021)
AbstractThe purpose of this study is to find parents' efforts to improve understanding in caring for children with mental retardation in Kendal district. The subjects of this study were parents who have mentally retarded children. This study uses a qualitative case study method. The data collection uses interview and observation technique and the technical data analysis uses descriptive analysis. The results of this study found that parents are lack of understanding in taking care children with mental retardation and parents need to improve their understanding of taking care children with mental retardation.Keywords: Improving Understanding, Caring for Children, and Children with Mental Retardation